The severe presentation and poor outcomes of rheumatic heart disease in Namibia: Lessons from the REMEDY study - T Auala; L Zühlke; L Sikwaya; H du Toit; G Karthikeyan; K Teo; S Yusuf; M E Engels; B M Mayosi; C T Hugo-Hamman (South African Medical Journal, 2023)
Background. This paper reports the baseline characteristics and outcomes of 266 Namibian patients in the Global Registry of Rheumatic Heart Disease. Objective. To describe clinical findings and outcomes in a cohort of children and adults with rheumatic heart disease in Namibia. Methods. Prospective study of all patients with rheumatic heart disease at Windhoek Central Hospital between January 2010 and November 2012. Results. A total of 266 patients were enrolled; median age was 22 years, 72.6% were <30 years old and 60.5% female. The majority (62.8%) had moderate-severe disease; 48.9% were in congestive cardiac failure. Secondary antibiotic prophylaxis was used by 34.2%. Warfarin was used by 75.3% (n=64/85) with clinical indications. Forty-seven (17.6%) had previous valve interventions, of whom 40 (15.0%) had mechanical valve replacements. Over a 2-year follow-up period 19.1% of patients died. Severe valve involvement at enrolment was independently associated with mortality (24.6% v. 5.1% in those without severe disease; hazard ratio 4.9; 95% confidence interval 1.50 - 15.98). Sixty-five (29.8%) of the 218 without previous intervention had valvular intervention after enrolment. Conclusions. In Namibia rheumatic heart disease affects young people who present with severe disease and have a high case fatality rate. Rates of secondary prevention were low. These findings have informed the National Programme for Prevention and Control of Rheumatic Heart Disease in Namibia.